DIE EERSTE BEGINSELS VAN DIE WOORD, DIE IMPLIKASIE VAN HEB 5:12 VIR KERK EN TEOLOGIE - Zuiddam, Benno Alexander (Scriptura, 2011)
Hebrews uses the words λογίων τοῦ θεοῦ to denote authoritative Divine speech. These are treated as oracles from heaven with an inherently divine quality. Hebrews’ use of λογίων as such implies a divine source and this is reinforced by τοῦ θεοῦ. Both the wider and narrower context of Hebrews 5:12 show that this expression is used in a context of revelation. God reaches out and speaks. In this context God’s oracles are presented as instrumental for maintaining this relationship with the divine and particularly portrayed as promoting spiritual growth and maturity. It is from this literary context, and the specific use of λογίων in Hebrews 5:12 that this article argues that the phrase τὰ στοιχεῖα τῆς ἀρχῆς τῶν λογίων τοῦ θεοῦ refers to the very elementary knowledge, or basic understanding of the "Word of God" or his collective "Oracles". Even the practice of these Oracle-basics is considered potentially life-changing and spiritually empowering by the author of Hebrews. Knowledge of God’s revelation, even a thirst for more, is presented as a basic requirement for Christian life.